Síntese de nanopartículas de CuO e aplicações catalíticas - Silva, Ermeson David dos Santos (2024)
Global population growth, reaching 8 billion people in November 2022, will continue to impose significant pressures on industrial production, agriculture, urban mobility, and energy demand. Coupled with the depletion of fossil fuels and the increasing need for renewable energy, H2 has emerged as a sustainable energy source due to its high energy content and low environmental impact. Water electrolysis for H2 and O2 production has been explored as an eco-friendly approach providing clean and easily transportable fuel for large industries. However, the development of efficient electrocatalysts based on metals such as Ni, Cu, Co, Fe, Mo and W is essential due to the high cost associated with platinum, one of the most efficient materials for the process. Among catalysts based on these materials, metal oxide nanoparticles, such as CuOx, stand out for their high efficiency in energy capture applications. However, corrosion poses a significant challenge for this material as the bandgaps of these materials may cover the oxidation/reduction potentials of water. In this study, electrocatalysts were developed using CuOx thin films, which were subjected to thermal treatment at 500°C and 600°C in atmospheres containing O2 and N2. Additionally, the effect of TiO2 coating as a protective layer against CuOx corrosion was investigated, with deposition carried out using ultraviolet radiation. Electrodes treated in N2 atmosphere at 600°C, with and without TiO2 coating, showed superior catalytic activity in the HER. Conversely, for the OER, samples treated in O2 atmosphere at 500°C and 600°C performed better. Electrodes produced in N2 atmosphere exhibited higher ESCA, indicating a greater number of active sites exposed to surface reactions. The results strengthen the idea that TiO2 acts as a protective layer, preventing rapid electron-hole recombination and thereby the rapid corrosion of CuOx.